PERANCANGAN ANIMASI IKLAN DIGITAL BERBASIS MOTION GRAFIS SEBAGAI PENUNJANG PROMOSI PADA PERMATA JAYA PRINTING - Setiyo Prihatmoko; M Syarif Husen; Sumaryanto, Sumaryanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Promotional strategies are used in marketing to determine the best way to bring products or services to certain markets, but sometimes in companies these strategies are often not optimal, as is still done by the printing and advertising company Permata Jaya Printing which only uses print media in the form of banners, posters , word of mouth and social media so that this promotional strategy is considered less effective in reaching a wider audience. To support the promotional media used by Permata Jaya Printing, the author tries to offer another alternative, namely the use of promotional media in the form of digital advertising videos based on motion graphics as a solution to this problem which is then distributed via social media. . Media such as Instagram and WhatsApp. The author chose to use the Research and Development (RnD) method in carrying out research which aims at the process of systematically searching for new knowledge, ideas, products and technologies, as well as developing and applying them to encourage innovation and growth. User efficacy test results were 83.5%. which is classified as very effective. So that this advertising video product can be declared feasible